Full recovery after 45 min of open cardiac massage for penetrating trauma: Resuscitation guided by end tidal CO2 and permissive hypotension. (December 2020) - Ang, Darwin; Weber, Courtney; Clark, Jason
Abstract: We present a rare case of a patient who sustained a gunshot wound to the abdomen, injuring the aorta, IVC and right common iliac vein. After initially obtaining return of spontaneous circulation (ROSC) en route to the hospital, the patient again lost cardiac activity in the operating room during exploratory laparotomy. Resuscitative thoracotomy was performed and open cardiac massage was maintained for approximately 45 min while vessel injuries were repaired. During cardiac massage, end tidal CO2 was maintained between 15 and 31 mm Hg with 100% oxygen saturation and the patient received on-going transfusion of recycled whole blood and blood component therapy. Permissive hypotension was maintained to facilitate rapid repair of major vessels. Return of spontaneous circulation was achieved with a single 30 joule defibrillation. The patient was discharged home on hospital day 11, neurologically intact. This is the first report of survival after 45 min of open cardiac massage with aortic cross clamping, indicating that end tidal CO2 may act as an indicator of adequate end organ perfusion during protracted periods of hypotension.